Early phase 2 trial of TAS‐205 in patients with Duchenne muscular dystrophy. Issue 2 (20th January 2020) - Komaki, Hirofumi; Maegaki, Yoshihiro; Matsumura, Tsuyoshi; Shiraishi, Kazuhiro; Awano, Hiroyuki; Nakamura, Akinori; Kinoshita, Satoru; Ogata, Katsuhisa; Ishigaki, Keiko; Saitoh, Shinji; Funato, Michinori; Kuru, Satoshi; et al.
Abstract: Objective: Duchenne muscular dystrophy (DMD) is a progressive muscular disease characterized by chronic cycles of inflammatory and necrotic processes. Prostaglandin D2 (PGD2 ) is produced by hematopoietic PGD synthase (HPGDS), which is pathologically implicated in muscle necrosis. This randomized, double‐blind, placebo‐controlled early phase 2 study (NCT02752048) aimed to assess the efficacy and safety of the novel selective HPGDS inhibitor, TAS‐205, with exploratory measures in male DMD patients aged ≥5 years. Methods: Patients were randomized 1:1:1 to receive low‐dose TAS‐205 (6.67–13.33 mg/kg/dose), high‐dose TAS‐205 (13.33–26.67 mg/kg/dose), or placebo. The primary endpoint was the change from baseline in a 6‐minute walk distance (6MWD) at Week 24. Results: Thirty‐six patients were enrolled, of whom 35 patients were analysed for safety. The mean (standard error) changes from baseline to Week 24 in 6MWD were −17.0 (17.6) m in the placebo group ( n = 10), −3.5 (20.3) m in the TAS‐205 low‐dose group ( n = 11), and −7.5 (11.2) m in the TAS‐205 high‐dose group ( n = 11). The mean (95% confidence interval) difference from the placebo group was 13.5 (−43.3 to 70.2) m in the TAS‐205 low‐dose group and 9.5 (−33.3 to 52.4) m in the TAS‐205 high‐dose group. No obvious differences were observed in the incidences of adverse events between treatment groups. No adverse drug reactions specific to TAS‐205 treatment were observed. Interpretation: The HPGDS inhibitor TAS‐205 showed a favorable safety profile in DMD patients. Further research is required to examine the effectiveness of TAS‐205 in a larger trial.